QUALITY OF LIFE AND COMPLIANCE TO THERAPY IN PATIENTS FOLLOWING SUCCESSFUL TRANSLUMINAL CORONARY ANGIOPLASTY, WHO WERE PRESCRIBED LESCOL XL (FLUVASTATIN) ADDED TO STANDARD THERAPY. RESULTS OF THE LESQOL OPEN-LABEL OBSERVATIONAL STUDY - A. V. Susekov; V. A. Bulatov; A. V. Vigdorchik (Рациональная фармакотерапия в кардиологии)
Aim. The main aim of the present study was to evaluate quality of life changes and compliance to therapy in patients following successful transluminal angioplasty, who were prescribed fluvastatin extended release in addition to standard treatment.Material and methods. This was a national prospective multicenter observational study. Patients with coronary heart disease following successful transluminal coronary angioplasty, who were prescribed fluvastatin extended release (Lescol Forte, Novartis) 80 mg QD were included in the present observation. The following efficacy and safety parameters were evaluated: quality of life evaluated with SF-36 scale before and during treatment; hypolipidemic efficacy, compliance to therapy; adverse events and serious adverse events. Observation period was 6 months in all patients and 12 months in some patients at the discretion of the investigator.Results. 524 patients (79% men and 21% women) completed the 6 months observation period and 116 patients were followed up for 12 months. Significant increase of all measures of SF-36 scales, physical and mental health was observed in 6 and 12 months of fluvastatin extended release treatment. Total and low density lipoprotein cholesterol reduction was 30.5% and 54.9% respectively, p<0.01, in 6 months and 34.2% and 34.3% respectively in 12 months of treatment, p<0.01. High density lipoprotein cholesterol was significantly increased by 22.5% in 12 months of treatment, p<0.01. There were very few adverse events and laboratory changes during the course of treatment.Conclusion. LESQOL study showed significant increase in quality of life and good hypolipidemic efficacy as well as good tolerability of fluvastatin extended release in patients after coronary angioplasty.